Assessment of cost of illness for diabetic patients in South Indian tertiary care hospital - Leelavathi D Acharya; N R Rau; N Udupa; M Surulivel Rajan; K Vijayanarayana (Wolters Kluwer Medknow Publications, 2016)
Background: The impact of diabetes on health-care expenditures has been increasingly recognized. To formulate an effective health planning and resource allocation, it is important to determine economic burden. Objective: The objective of this study is to assess the cost of illness (COI) for diabetic inpatients with or without complications. Methodology: The study was conducted in the medicine wards of tertiary care hospital after ethical approval by the Institutional Ethical Committee. A total of 116 each diabetic with or without complications were selected and relevant data were collected using COI questionnaire and data were analyzed using SPSS version 20. Mann-Whitney U test is used to assess the statistical significant difference in the cost of treatment of diabetes alone and with complications'. P ≤ 0.05 was considered statistically significant. Results: Total COI includes the cost of treatment, investigation, consultation fee, intervention cost, transportation, days lost due to work, and hospitalization. The median of total COI for diabetic care without any complication was Rs. 22,456.97/- per patient per annum and with complication was Rs. 30,634.45/-. Patients on dialysis had to spend 7.3 times higher, and patients with cardiac intervention had to spend 7.4 times higher than diabetic patients without any complication. Conclusion: Treatment costs were many times higher in patients with complications and with cardiac and renal interventions. Complications in diabetic patients will increase the economic burden to family and also to the society.